Retinal pigment epithelial integrity is compromised in the developing albino mouse retina. Issue 18 (19th May 2016) - Iwai‐Takekoshi, Lena; Ramos, Anna; Schaler, Ari; Weinreb, Samuel; Blazeski, Richard; Mason, Carol
ABSTRACT: In the developing murine eye, melanin synthesis in the retinal pigment epithelium (RPE) coincides with neurogenesis of retinal ganglion cells (RGCs). Disruption of pigmentation in the albino RPE is associated with delayed neurogenesis in the ventrotemporal retina, the source of ipsilateral RGCs, and a reduced ipsilateral RGC projection. To begin to unravel how melanogenesis and the RPE regulate RGC neurogenesis and cell subpopulation specification, we compared the features of albino and pigmented mouse RPE cells during the period of RGC neurogenesis (embryonic day, E, 12.5 to 18.5) when the RPE is closely apposed to developing RGC precursors. At E12.5 and E15.5, although albino and pigmented RPE cells express RPE markers Otx2 and Mitf similarly, albino RPE cells are irregularly shaped and have fewer melanosomes compared with pigmented RPE cells. The adherens junction protein P‐cadherin appears loosely distributed within the albino RPE cells rather than tightly localized on the cell membrane, as in pigmented RPE. Connexin 43 (gap junction protein) is expressed in pigmented and albino RPE cells at E13.5 but at E15.5 albino RPE cells have fewer small connexin 43 puncta, and a larger fraction of phosphorylated connexin 43 at serine 368. These results suggest that the lack of pigment in the RPE results in impaired RPE cell integrity and communication via gap junctions between RPE and neural retina during RGC neurogenesis. Our findings should pave the way for further investigation of the role of RPE in regulating RGC development toward achieving proper RGC axon decussation. J. Comp. Neurol. 524:3696–3716, 2016. © 2016 Wiley Periodicals, Inc. Abstract : In albinism, ipsilateral retinal ganglion cells (RGCs) are reduced. To dissect how melanin affects visual pathway development, we compared embryonic albino and pigmented retinal pigment epithelium (RPE). The perturbations of albino RPE cells charted here could affect RPE integrity and communication with neural precursors during RGC differentiation.